Perancangan Sistem Pemanas Bearing Menggunakan Kontrol Pi Berbasis Mikrokontroler Atmega 8535 - Sumardi, Sumardi; Setiawan, Iwan; Purwanto, Sigit (Departemen Teknik Elektro, Universitas Diponegoro, 2008)
Bearing is an important component of motor and generator, bearing is used as a buffer component of shaft rotor that has function to decrease the friction between shaft rotor and housing. The damaging on a bearing can make an increasing of power consumption and a big friction that can make many vibrations and uproar in the motor or generator.Based on SKF’s research, 16% of the bearing’s initial damage is caused by the wrong assembling method. For example the installation of the bearing in the shaft is forcefully, by hits or burns them use the asetelin weld. The heating of bearing uses assetelin, isen’t good. Because the heat is not be stread evenly. So in order to get heating is average in bearing, we use induction heat.This making final assignment is to make a bearing heater which use induction method with digital PI control induction method. With Microcontroller ATmega 8535 as a digital code’s processor and as their controller. This instrument can raise the increasing linear temperature and the average heat. Beside that, the temperature of the heated bearing also can be kept on interval 80° - 90°C. With this instrument, the diameter of the heated bearing can expand, the heating is average and the bearing temperature can be controlled, so the bearing can be installed in the shaft rotor easily.Key Words: Bearing heater, PI control, Microcontroller ATmega 8535